Areca nut - an unusual cause of small intestinal obstruction - Akhtar, Murtaza; Deshpande, Gayatri; Daware, Ankit (Indian Journal of Case Reports, 2018)
Ingested foreign bodies are commonly encountered in clinical practice, especially in children. Till now, no case has been reported in the literature where a small intestinal obstruction was produced as a result of foreign body (areca nut) ingestion. We report a case of a 30-year-old female clinically presented as an acute intestinal obstruction of 4 days duration. Her plain X-ray abdomen showed multiple small intestinal fluid levels. Abdominal ultrasound showed dilated loops of small intestine. Contrast-enhanced computed tomography abdomen showed an intraluminal non-enhancing lesion near ileocecal junction. Exploratory laparotomy revealed 3 cm